"An Oppressive Insensibility": Disestablishment, Clerical Infirmity, and the Origins of the Manual Labor Movement. Issue 4 (December 2022) - Stokum, Christopher J.
Abstract : In the contested spiritual economy of the early nineteenth century, recently disestablished American clergymen consolidated themselves in theological seminaries. Members of the dominant New England Congregationalist and Presbyterian ministries, these seminarians organized a defensive front against itinerant, populist rivals by intensifying their curricula, proscribing physical exertion as a distraction from study, and shielding clerical students from popular influence. Yet critical voices from within the seminaries soon reported that unrelenting study damaged students' bodily health and alienated the clergy from a laity on whom their educational funding now depended. Accompanying such critiques were proposals for an alternative pedagogy that gained its fullest expression in the manual labor school, where physical vigor was enshrined as a complement to theological training and where barriers separating clergy from laity were minimized. By situating the infirmities that seminarians logged in memoirs and exposés alongside their efforts to reform the seminary system, this article argues that the graduate clergy mustered a coherent, forceful response to the crisis in spiritual leadership that disestablishment precipitated. The article presents clerical elites not as casualties of democratization or as agents of capital, but as self-aware and self-interested economic actors in the reordering of American religious authority after disestablishment.